Multivariate Analysis of Noise, Socioeconomic and Sociodemographic Factors and Their Association with Depression on Borough Level in the City State of Hamburg, Germany - Caroline Krefis, Anne; Albrecht, Myriam; Kis, Anne; Langenbruch, Anna; Augustin, Matthias; Augustin, Jobst (Journal of Depression And Therapy, 2017)
The objective of this first part of our study was to investigate associations of road traffic noise, socioeconomic and -demographic risk factors, and health access on depression on borough level. We investigated in a large metropolis associations between prevalence rates of depression per borough (n = 67 boroughs) in all age groups (excluding the age group of 0–17 years) using health claims data (year 2011) and the variables “social deprivation” and “number of family members”, which were obtained from a previously conducted principal component analysis, and by using multivariate regression model. Additionally, the proportion of borough area affected by noise > 65 db(A) and physician density used as a surrogate parameter for health access were considered as potentially associated factors for depression. The results demonstrated that depression might be associated with increasing social borough deprivation. Additionally, the number of family members used as a proxy measure for positive family support showed decreasing prevalence rates the more family members were present. Furthermore, proportions of borough areas affected by noise > 65 db(A) was positively associated with depression. Our ecological study design has the advantage that a large number of large-scale, population-based aggregated data could easily be obtained and analysed and first potential associations could be found and discussed. To improve our findings, future studies will use data from a survey and data from the Hamburg City Health Study, a local follow-up health study, to better elucidate the individual risk factors together with environmental living and working conditions.
Keywords: Socioeconomic Factors; Depression; Noise; Urban Spatial Distribution; Spatial Analysis